2011
DOI: 10.1590/s0102-33062011000200020
|View full text |Cite
|
Sign up to set email alerts
|

Morfoanatomia de órgãos vegetativos de plantas juvenis de Aegiphila sellowiana Cham. (Lamiaceae) submetidas ao alagamento do substrato

Abstract: ABSTRACT(Morpho-anatomy of vegetative organs in seedlings of Aegiphila sellowiana Cham. (Lamiaceae) subject to flooding). In order to uncover the morpho-anatomical responses of tree species to hypoxia, we studied the effects of flooding on vegetative organs of Aegiphila sellowiana. Young individuals were kept in drained and flooded soil for 50 and 80 days. Under flooding, there was a mortality rate of 40%. The surviving plants produced peridermic fissures, superficial roots and hypertrophied lenticels. Seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(51 reference statements)
0
3
0
5
Order By: Relevance
“…The thick, waxy cuticle provided greater protection in this study because the waterlogged plants exhibited lower water potential (Medri et al., 2011). Metcalfe and Chalk (1950) identified distinct types of vascular structures in petioles of Clusiaceae, where the vascular bundles of Garcinia mangostana L. were completely closed tubes surrounded by collateral bundles; however, it was observed that the bundles in the petiole of Garcinia madruno have a semicircular cylindrical shape.…”
Section: Anatomymentioning
confidence: 77%
“…The thick, waxy cuticle provided greater protection in this study because the waterlogged plants exhibited lower water potential (Medri et al., 2011). Metcalfe and Chalk (1950) identified distinct types of vascular structures in petioles of Clusiaceae, where the vascular bundles of Garcinia mangostana L. were completely closed tubes surrounded by collateral bundles; however, it was observed that the bundles in the petiole of Garcinia madruno have a semicircular cylindrical shape.…”
Section: Anatomymentioning
confidence: 77%
“…seedlings after 15 days of flooding, similar to what was observed for S. terebinthifolia seedlings. The reduction in number of leaves under flooding as a response to the increase in ethylene in the leaf tissue, promoting leaf abscission (Medri et al, 2011). As for chlorophyll indices, flooding had little influence, but the foliar application of 1.0 and 3.0 mM of Si and SA, respectively, favored the maintained synthesis of photosynthetic pigments.…”
Section: Discussionmentioning
confidence: 99%
“…Las raíces de las plantas producidas con exceso de humedad reducen la capacidad de las mismas de realizar intercambios gaseosos y de absorber agua y nutrientes, una vez que la planta reduce la transpiración y, consecuentemente, el metabolismo es perjudicado, habiendo reducción de su crecimiento (Medri et al 2011).…”
Section: Regímenes De Riegounclassified
“…De acuerdo con Medri et al (2011), plantas sometidas al exceso de humedad presentan reducción en la tasa de crecimiento relativo, en función de la caída en la tasa fotosintética, con la consecuente reducción en la producción de fotoasimilados.…”
Section: Regímenes De Riegounclassified